2018
DOI: 10.3390/fluids3030049
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Aerodynamic Sealing of Air Curtains

Abstract: Abstract:Controlling the air quality is of the utmost importance in today's buildings. Vertical air curtains are often used to separate two different climatic zones with a view to reduce heat transfer. In fact, this research work proposes an air curtain aimed to ensure a proper separation between two zones, a clean one and a contaminated one. The methodology of this research includes: (i) small-scale tests on water models to ensure that the contamination does not pass through the air curtain, and (ii) an analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…That is to say, a plane jet that ensures minimum (optimized) exhaust flowrates from the contaminated compartment or that supplies minimum (optimized) flowrates to the non-contaminated compartment, and ultimately reduces the air treatment costs. This research encompasses three phases, namely: (i) small-scale experiments using water as the work fluid 10 ; (ii) computational fluid dynamics (CFD) simulations to verify if the small-scale test results are applicable to full size air curtains 11 ; and (iii) full-size air curtain experiments. The full-size experiments were subdivided in two sets of tests, namely: (iiia) assessment of the aerodynamic sealing for PM10 and comparison with the visual assessment and (iiib) optimisation of the aerodynamic sealing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is to say, a plane jet that ensures minimum (optimized) exhaust flowrates from the contaminated compartment or that supplies minimum (optimized) flowrates to the non-contaminated compartment, and ultimately reduces the air treatment costs. This research encompasses three phases, namely: (i) small-scale experiments using water as the work fluid 10 ; (ii) computational fluid dynamics (CFD) simulations to verify if the small-scale test results are applicable to full size air curtains 11 ; and (iii) full-size air curtain experiments. The full-size experiments were subdivided in two sets of tests, namely: (iiia) assessment of the aerodynamic sealing for PM10 and comparison with the visual assessment and (iiib) optimisation of the aerodynamic sealing.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the scope of this project it was necessary to develop the research on the isothermal case, which is considered a limit condition. Previous isothermal work, carried out in the framework of this project, showed that the aerodynamic sealing could be obtained on a small-scale test rig 10 and the corresponding physical laws were developed. It was also shown, by Computational Fluid Dynamics (CFD), that this aerodynamic sealing could be expected for full-size applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the transport of airborne pollutants (which, in general, may include microorganisms, bacteria, fungus, particles), the air is extracted from the contaminated compartment, which induces a flow crossing the air curtain. This behaviour, in specific conditions, may avoid the flow to be released from the contaminated compartment to the non-contaminated side at the jet impinging zone, as shown in Figure 1 (see Section 2.1 of reference [26] for a more detailed analysis). The air extracted from the contaminated compartment should be decontaminated.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the exhaust flow rate that provides aerodynamic sealing under different air curtain characteristics, a research program was established, consisting of the following phases: (i) small-scale experiments using water as the work fluid [26]; (ii) Computational Fluid Dynamics (CFD) simulations to verify if the small-scale test results were applicable to a full-size air curtains [28]; (iii) full-size air curtain experiments. The full-size experiments were subdivided into two sets of tests, namely: (iiia) assessment of the aerodynamic sealing for PM10 and comparison with the visual assessment [27] and (iiib) optimisation of the aerodynamic sealing for low Reynolds number jet velocities.…”
Section: Introductionmentioning
confidence: 99%